The Ugly: Metastatic Colon Cancer—Surgical Options - Dossa, Fahima; Weiser, Martin R. (Clinics in Colon and Rectal Surgery, 2024)
Over 50% of patients with colorectal cancer develop metastatic disease. Although systemic therapy remains the backbone of palliative treatment, select patients may be candidates for surgical resection with curative intent. Given increasing evidence of the association between metastasectomy and prolonged survival, surgery has acquired an increasingly central role in the management of liver, lung, and peritoneal metastases. This is compounded by accumulating advances in local and systemic treatments that have allowed for expansion of the resectability pool, bringing the potential for curative surgical treatment to increasing numbers of patients with stage IV disease. However, as the boundaries of resectability are pushed, patient selection and consideration of tumor-related and technical factors are imperative to the identification of patients for whom surgery would be of the greatest benefit.
Keywords: colorectal cancer; metastasis; resection; survival